Production of β-galactosidase from streptococcus thermophilus for galactooligosaccharides synthesis - Sangwan, Vikas (J Food Sci Technol, 2014)
Efficiency of different methods for disruption of Streptococcus thermophilus cells, isolated from different dairy products, to release β-galactosidase and synthesis of GOS by extracted enzyme using whey supplemented with different concentrations of lactose as a substrate was studied. Unlike most other studies on GOS synthesis which used only one method of cell disruption and only few microbial strains, we compared five different cell disruption methods and used 30 strains of S. thermophilus in order to find out the most effective method and efficient strain for production of β-galactosidase. Appreciable amount of GOS (53.45 gL(−1)) was synthesized at a lactose concentration of 30 %, using enzyme (10 U mL(−1) of reaction medium), extracted from S. thermophilus within a very short incubation time of 5 h at a temperature of 40 °C and pH 6.8. S. thermophilus is heavily employed in the preparation of fermented dairy products but this study extends the use of this organism for the production of GOS, a potential prebiotic.